The Great War in the Heart of Dixie : Alabama During World War I - Olliff, Martin T. (Book collections on Project MUSE., 2015)
There has been much scholarship on how the U.S. as a nation reacted to World War I, but few have explored how Alabama responded. Did the state follow the federal government's lead in organizing its resources or did Alabamians devise their own solutions to unique problems they faced? How did the state's cultural institutions and government react? What changes occurred in its economy and way of life? What, if any, were the long-term consequences in Alabama? The contributors to this volume address these questions and establish a base for further investigation of the state during this era. Contrib.